IMF flexibility or neoliberal adaptation: A discursive content analysis of Article IV policy biases in Argentina. Issue 1 (31st March 2019) - Hernandez, Christian
Abstract : At the turn of the century, the consensus among scholars was that the International Monetary Fund's (IMF) policy preferences, which centered on deflation via austerity, privatization, and deregulation, were indicative of its neoliberal bias. However, a subsequent wave of literature has challenged this view by suggesting that the IMF has demonstrated flexibility. While these accounts arrive at their conclusion via different analytical and empirical focuses, this article posits that the flexibility or breath of ideas found within the discourse itself is key to gauging policy biases (previous study). Herein, this article contributes to the question of whether the IMF can be considered a "flexible" institution via its analysis on Argentina (1989–2006; 2016–2017). Extending a previous study's methods, this one provides a "discursive content analysis, " on the IMF–Argentine Article IV consultations. Ultimately, the findings show that policy discourse remained neoliberal throughout.